Tolerance of Vascularized Islet‐Kidney Transplants in Rhesus Monkeys. Issue 1 (9th August 2016) - Pathiraja, V.; Villani, V.; Tasaki, M.; Matar, A. J.; Duran‐Struuck, R.; Yamada, R.; Moran, S. G.; Clayman, E. S.; Hanekamp, J.; Shimizu, A.; Sachs, D. H.; Huang, C. A.; et al.
Abstract : We previously reported that transplantation (Tx) of prevascularized donor islets as composite islet‐kidneys (IK) reversed diabetic hyperglycemia in both miniature swine and baboons. In order to enhance this strategy's potential clinical applicability, we have now combined this approach with hematopoietic stem cell (HSC) Tx in an attempt to induce tolerance in nonhuman primates. IKs were prepared by isolating islets from 70% partial pancreatectomies and injecting them beneath the autologous renal capsule of five rhesus monkey donors at least 3 months before allogeneic IK Tx. HSC Tx was performed after mobilization and leukapheresis of the donors and conditioning of the recipients with total body irradiation, T cell depletion, and cyclosporine. One IK was harvested for histologic analysis and four were transplanted into diabetic recipients. IK Tx was performed either 20–22 (n = 3) or 208 (n = 1) days after HSC Tx. All animals accepted IKs without rejection. All recipients required >20 U/day insulin before IK Tx to maintain <200 mg/dL, whereas after IK Tx, three animals required minimal doses of insulin (1–3 U/day) and one animal was insulin free. These results constitute a proof‐of‐principle that this IK tolerance strategy may provide a cure for both end‐stage renal disease and diabetes without the need for immunosuppression. Abstract : The authors report the successful use of transient mixed hematopoietic chimerism to induce tolerance of composite islet‐kidneys across a one‐haplotype major histocompatibility complex barrier in rhesus monkeys.